Supramolecular Interactions between Library Members Modulate the Behavior of Dynamic Combinatorial Libraries - Orrillo, Alfredo Gastón (2010)
The presence of a supramolecular network of interactions between library members can lead to very different responses when libraries with identical molecular composition are exposed to the same template. Numerical simulations demonstrate that supramolecular interactions between library members of covalent dynamic combinatorial libraries (DCLs) can affect both degree and selectivity of the response of the library when a template molecule is added.